Assessment of stress tolerance and fermentation performance in traditional Norwegian Landrace (Kveik) yeast - Isbell, Todd (2023)
Kveik yeast are believed to constitute a subspecies of Saccharomyces cerevisiae used by rural Norwegian brewers to brew traditional ales for personal and ceremonial consumption. These yeasts have remained largely unexplored until recent times, where their potential for use in mainstream beer production has been realised. Due to the nature of their origins and use, kveik cultures often comprise multiple strains, although single-strain isolates have been identified. Irrespective of their composition, the advantage of kveik yeast is that they ferment rapidly at high temperatures and, under these conditions, produce a relatively neutral flavour contribution when compared to contemporary brewers yeasts. However, a full understanding of the properties and potential for kveik strains has yet to be achieved.